Transformerless high gain boost and buck-boost DC-DC converters based on extendable switched capacitor (SC) cell for stand-alone photovoltaic system - Amir, Asim; Che, Hang Seng; Amir, Aamir; El Khateb, Ahmad; Rahim, Nasrudin Abd (Elsevier, 2018)
This paper presents transformerless high gain boost and buck-boost DC-DC converters (B-BBCs) with extendable switched capacitor cells (SCs), suitable for applications operating at high voltage, above 300 V. Boosting low voltage to a high-enough level, with low duty ratio, is beyond the practical capability of the conventional boost converter. In addition, high duty ratio needed for operation of the boost converter, results in higher component stress that suppresses the overall efficiency of the converter. Therefore, by a convenient integration of SCs with conventional B-BBCs, increased voltage gain is attained with fewer losses. Such converters can be employed for Photovoltaic (PV) systems. The operational principles and modes of operation are analyzed to justify the utility of converters for stand-alone PV systems. Moreover, the proposed modular structure allows to increase SC cells in order to obtain reduced voltage stress on switching components with a higher voltage gain. Simulation and experimental results based on 100 W laboratory prototype extol the theoretical analysis.